Self-Inflicted Wounds. The 2013 Government Shutdown And The Internal Divisions Of Congressional Republicans - Klemetti, Anssi (fi=Turun yliopisto|en=University of Turku|, 2017)
The aim of this thesis is to look into the 2013 government shutdown in the United States of America, which lasted from October 1 to October 16, with the purpose of studying the internal divisions that were created or made visible within the Congressional manifestation of the Republican Party. The main sources for the thesis are a pair of shutdown-inducing letters from Mark Meadows and Mike Lee to Congressional leaders, the final tallies of the votes that ended the shutdown, as well as media sources. The initial shutdown-related division was made apparent in the summer of 2013 between the 14 Senators and 80 Representatives supporting through the Meadows and Lee letters a "defunding strategy", which ultimately led to the shutdown, and the 32 Senators and 152 Representatives who opposed using said strategy to combat President Obama's healthcare reform. The final division was between the 18 Senators and 144 Representatives who opposed the final compromise that ended the shutdown and the 27 Senators and 87 Representatives who voted in favor of reopening the government. Republicans who did not sign one of the letters and who voted for the final compromise were more likely to have experience of previous government shutdowns; more likely to have seniority over their colleagues; more likely to be ideologically moderate; less likely to be affiliated with the Tea Party; and more likely to hail from competitive districts or states, while the opposite is true for the Republicans who had signed one of the letters and who opposed the final compromise. While Congressional leaders like John Boehner and Mitch McConnell were largely successful in navigating the crisis, it was the leading defunder Ted Cruz in particular who benefited from the national attention that resulted from the shutdown. While the Tea Party movement was a necessary precondition for elevating politicians such as Cruz, the shutdown crisis should not be understood as an event caused by the Tea Party alone.

Pro gradu -työ tutkii Yhdysvalloissa lokakuussa 2013 puhjennutta kuusitoistapäiväistä hallintosulkukriisiä ja erityisesti niitä republikaanipuolueen sisäisiä jakolinjoja, jotka syntyivät tai paljastuivat kongressissa kriisin myötä. Tutkielman päälähteinä käytetään Mark Meadowsin ja Mike Leen kongressijohtajille lähettämiä hallintosulkuun johtaneita kirjeitä, hallintosulun päättäneiden kongressiäänestysten tuloksia sekä medialähteitä. Ensimmäinen hallintosulkuun liittyvä jakolinja republikaanien joukoissa ilmeni vuoden 2013 kesällä erimielisyytenä strategiasta, jolla presidentti Barack Obaman terveydenhuoltouudistusta pitäisi vastustaa: 14 senaattoria ja 80 edustajainhuoneen jäsentä kannattivat Meadowsin ja Leen kirjeissä peräänkuulutettua ”rahoituksen leikkaus” -strategiaa, kun taas 32 senaattoria ja 152 edustajainhuoneen jäsentä vastustivat strategiaa. Hallintosulkukriisin lopettaneen kompromissiäänestyksen yhteydessä republikaanien lopulliseksi jakolinjaksi jäi 18 senaattoria ja 144 edustajainhuoneen jäsentä kompromissia vastaan ja 27 senaattoria ja 87 edustajainhuoneen jäsentä kompromissin puolesta. Meadowsin tai Leen kirjeen allekirjoittamatta jättäneet ja loppukompromissia kannattaneet republikaanit olivat kollegoitaan todennäköisemmin aikaisempien hallintosulkujen veteraaneja, muutenkin virkaiältään kollegoitaan vanhempia, ideologialtaan maltillisempia, tiukemmin kilpailtujen vaalipiirien edustajia sekä vähemmän todennäköisesti kytköksissä teekutsuliikkeeseen – päinvastaisen ollessa totta jomman kumman kirjeen allekirjoittaneista ja loppukompromissia vastustaneista republikaaneista. Vaikka republikaanijohtajat John Boehner ja Mitch McConnell onnistuivatkin melko hyvin hallintosulkukriisin polittisissa ristipaineissa navigoinnissa, kriisistä hyötyi eniten ”rahoituksen leikkaus” -strategian näkyvin äänenkannattaja Ted Cruz, joka nousi kriisin myötä korkeaprofiiliseksi poliitikoksi. Vaikka teekutsuliike olikin välttämätön edellytys Cruzin kaltaisten poliitikkojen valtaannousulle, ei vuoden 2013 hallintosulkukriisiä tule pitää pelkästään teekutsuliikkeen aikaansaannoksena.
Itseaiheutettuja haavoja. Vuoden 2013 hallintosulku ja kongressin republikaanien sisäiset ristiriidat